KEMAMPUAN PEMASARAN DIGITAL, DIMEDIASI PENGGUNAAN CHATBOT UNTUK MENINGKATKAN MANAJEMEN HUBUNGAN PELANGGAN (CRM) DI SEKTOR ASURANSI JIWA - Afif Deni Irawan (2024)
This research explores the role of several marketing elements, including Chatbot, Content Marketing, Online Advertisement, and Usage of Social Media, in managing customer relationships (CRM) in insurance companies after the COVID-19 pandemic. .Data was obtained through a questionnaire. The total sample of 398 were personal customers who directly felt the effects of insurance services, then analyzed using the Structural Equation Modeling (SEM) method with SMARTPLS. The results of data analysis show that the use of chatbots has an important role in decisions to purchase insurance services. Even though Content Marketing does not directly affect CRM, it is still an important factor in encouraging customers to use Chatbots when transacting with insurance companies. Apart from that, persuasive online advertisements and effective use of social media influence the use of chatbots and CRM for insurance services. However, there is one hypothesis that is rejected, indicating that there is complexity in the relationship between marketing variables.